1986
DOI: 10.1111/j.1471-4159.1986.tb12994.x
|View full text |Cite
|
Sign up to set email alerts
|

H2 Histamine Receptors on the Epithelial Cells of Choroid Plexus

Abstract: A major site of cerebrospinal fluid production in vertebrates is the choroid plexus. The epithelial cells of the choroid plexus accumulate intracellular cyclic AMP in response to several effectors, including histamine. Since histamine is known to regulate fluid secretion in the stomach via H2 histamine receptors, we asked whether H2 receptors might also be present on epithelial cells of bovine choroid plexus. Using agonists and antagonists of histamine, we show that an agonist and antagonist pair specific for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The CP, located at different sites of the third (3V), fourth (4V) and lateral ventricles (LV; Wolburg and Paulus, 2010), is the site of production of the cerebrospinal fluid (CSF), which transports essential molecules throughout the nervous system. The CP contains receptors for 5HT (Watson et al, 1995) and HA (Crook et al, 1986), and both neurotransmitters influence metabolism in this area (Crook et al, 1984, Watson et al, 1995); the route may be through their direct release into the CSF as suggested by studies that report the presence of histaminergic (Ericson et al, 1987, Tillet et al, 1998) and serotonergic (Lorez and Richards, 1973, Chan-Palay, 1976) axons or dendrites in close proximity to the ventricles.…”
Section: Introductionmentioning
confidence: 99%
“…The CP, located at different sites of the third (3V), fourth (4V) and lateral ventricles (LV; Wolburg and Paulus, 2010), is the site of production of the cerebrospinal fluid (CSF), which transports essential molecules throughout the nervous system. The CP contains receptors for 5HT (Watson et al, 1995) and HA (Crook et al, 1986), and both neurotransmitters influence metabolism in this area (Crook et al, 1984, Watson et al, 1995); the route may be through their direct release into the CSF as suggested by studies that report the presence of histaminergic (Ericson et al, 1987, Tillet et al, 1998) and serotonergic (Lorez and Richards, 1973, Chan-Palay, 1976) axons or dendrites in close proximity to the ventricles.…”
Section: Introductionmentioning
confidence: 99%
“…Probability of significant difference from the PIA: *p < 0.05, *'p .= 0.01, and "'p < 0.001, tamine stimulates gastric acid secretion and heart rate and inhibits uterine contractions (Black et al, 1972). Secretory effects of histamine have been found to be exerted only through H2 receptors (Crook et al, 1986). Primary cultures of epithelial cells prepared from bovine choroid plexus have been found to possess receptors for isoproterenol, prostaglandin El , Shydroxytryptamine, and histamine (Crook et al,198 1).…”
Section: Discussionmentioning
confidence: 99%
“…Crook et al (1984) have proved that histamine stimulated the production of cyclic AMP by the choroid plexus epithelial cell. This stimulation of cyclic AMP production may be mediated via histamine H2 receptors located on the choroid epithelial cell (Crook et al, 1986). However, a role for histamine in the control of CSF production by the choroid plexus has not yet been established.…”
mentioning
confidence: 99%
“…This pathway may mediate the H 2 receptor-induced ERK2 activation observed in vitro in hippocampal CA3 cells [220]. In the brain, the cAMP response mediated by H 2 receptors occurs predominantly in neurons, but it was also evidenced in astrocytes [221], epithelial cells of choroid plexus [222], and microvessel-enriched preparations [223]. Recombinant H 2 receptors also activate cAMP-independent signaling pathways and induce an increase in inositol phosphate release and intracellular Ca 2 þ concentration [224], a PKC-dependent c-fos activation [225], and a PKA-and PKC-independent c-jun activation [226].…”
Section: Responses In Brainmentioning
confidence: 99%